Hypertension and Life-Threatening Bleeding in Children with Relapsed Acute Myeloblastic Leukemia Treated with FLT3 Inhibitors - Deniz Yılmaz Karapınar; Nihal Karadaş; Zühal Önder Siviş; Can Balkan; Kaan Kavaklı; Yeşim Aydınok (Turkish Journal of Hematology, 2015)
Experiences with new multikinase inhibitors are limited, especially in children. In this report we summarize our experience with 2 patients with relapsed acute myeloblastic leukemia (AML), one with FMS-like tyrosine kinase- 3-internal tandem duplication mutation and the other with a single base mutation (D835Y). Both patients received sorafenib, one for 19 days and the other for 42 days, with clofarabine-including chemotherapy. One additionally received sunitinib for a total of 20 days. Both patients developed severe pancytopenia, hypertension, life-threatening bleedings from the gastrointestinal system, and, finally, intrapulmonary hemorrhage. Although both reached severe aplasia of the bone marrow without blastic infiltration, death occurred with neutropenic sepsis.